Circ-malat1 promotes gastric cell growth via miR-154-5p/CCND2 - Li, Lina; Yang, Liuqing; Wang, Yuzhen; Nan, Kejun (Frontiers in Genetics, 2025)
Recent studies have shown that circular RNA (circRNA) plays an important role in the development of gastric cancer. However, despite the widespread use of high-throughput sequencing technologies, the function of many circRNAs in gastric cancer remains unclear. In this study, we selected a circ_0002082 (circ-malat1) that is differentially expressed between normal gastric epithelial cells and gastric cancer cells to further investigate its role and molecular mechanisms in regulating gastric cancer development. The study primarily explores the function and molecular mechanisms of circ-malat1 at the cellular and molecular levels. Functional studies reveal that overexpression of circ-malat1 promotes gastric cancer cell growth. Conversely, silencing the expression of circ-malat1 has the opposite effect. Mechanistic studies indicate that circ-malat1 is predominantly expressed in the cytoplasm of gastric cancer cells and can act as a competing endogenous RNA by sequestering miR-154-5p, thereby enhancing CCND2 gene expression. In conclusion, circ-malat1 promotes the development of gastric cancer by competitively binding to miR-154-5p. Based on literature reports, it is speculated that circ-malat1 may also participate in regulation through other pathways, which require further investigation.